ESTIMATED ACCURACY COMPARISON OF FETAL WEIGHT BETWEEN JOHNSON TOSHACH FORMULA AND DARE FORMULA TOWARDS BABIES BIRTH WEIGHT - Dewi Nur Hidayah; Sinar Pertiwi; Etin Rohmatin (Midwifery and Nursing Research, 2019)
Background: The estimated accuracy of birth weight is a key element in early labor. The accurate fetal weight prediction method is an act of preventive to overcome the complications that are expected to reduce morbidity and mortality in childbirth. Purpose: To determine the comparison of the estimated accuracy fetal weight between the Johnson Toshach formula and Dare formula against the baby's birth weight. Method: This study is an analytic survey with a cross-sectional in Labour Room and Perinatology of Dr.Soekardjo hospitals in January and February 2019. The sample in this study using purposive sampling totally 96 respondents. Data analysis was performed by univariate and bivariate using paired t-test, independent t-test. Results: There is no difference in fetal weight estimation between Johnson Toshach formula and Dare formula with the birth weight (ρ value> 0.1). The results of the diagnostic test for Johnson Toshach formula provides the accuracy (87.5%) and the Dare formula (91.7%). Conclusion:Dare formula is more accurate in determining the estimated fetal weight compared to Johnson Toshach formula.